The philosophical works of Francis Bacon: Methodized, and made English, from the originals, with occasional notes, to explain what is obscure; and shew how far the several plans of the author, for the advancement of all the parts of knowledge, have been executed to the present time - Bacon, Francis (J.J. and P. Knapton [etc.], 1733)
v. 1. A summary view of the author's life. Instauration, pt. 1: De augmentis scientiarum. Supplements to De augmentis scientiarum: The new Atlantis. A specimen of the history of Great Britain. Lives; or, Civil characters of Julius Caesar, Augustus Caesar, King Henry VII and Queen Elizabeth. Select speeches on particular occasions. Select letters upon various occasions. A collection of apophthegms. De sapientia veterum.- v. 2. Continuation of supplements to De augmentis scientiarum: A specimen of the Persian magick. A specimen of animated astronomy. A short scientifical critique on the works of the more eminent philosophers. Interiora rerum. A discourse of war. The prudent statesman. A proposal for a new digest of the laws of England. A history of the nature, use, and proceedings of the laws of England. Characteristicks of a believing Christian. An attempt to promote the peace of the Church. Instauration, pt. 2: Novum organum scientiarum. Appendix ... containing some intimations for prefecting the Novum organum.- v. 3. Instauration, pt. 3: Sylva sylvarum. Instauration, pt. 4: Scala intellectus: The history of life and death. A draught for the particular history of the wind. A plan for the particular history of condensation and rarifaction. Instauration, pt. 5: Philosophia prima. Appendix to the fifth and sixth parts of the Instauration.